A Investigating The Phenomenon of Jumper in Gen Z in The Banking Sector - Elysia, Dina; Purnama Sari, Desak Made Febri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to understand the phenomenon of “job hopping” among Generation Z employees in the banking sector, specifically at CIMB Niaga Bali Denpasar Branch. The research findings indicate that internal factors, such as discrepancies between job expectations and reality, monotony in tasks, limited personal development opportunities, and a lack of non-material recognition, influence Gen Z’s desire to switch jobs. External factors, including unsupportive work environments, unsupportive leadership, and rigid organizational structures, also contribute to this phenomenon. Socio-cultural factors, such as the influence of friends and family, as well as exposure to social media, also affect their decisions. The study concludes that job hopping among Gen Z is not a spontaneous phenomenon but rather a result of mismatches between job expectations and reality, as well as unsupportive work environments.. For companies, it is recommended to foster a supportive work environment, provide career development opportunities, and offer appropriate recognition. For Gen Z, it is advised to develop adaptability skills and choose companies that align with personal values.